5(2x-3)=(2x+x)(8-4)

Simple and best practice solution for 5(2x-3)=(2x+x)(8-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(2x-3)=(2x+x)(8-4) equation:



5(2x-3)=(2x+x)(8-4)
We move all terms to the left:
5(2x-3)-((2x+x)(8-4))=0
We add all the numbers together, and all the variables
5(2x-3)-((+3x)4)=0
We multiply parentheses
10x-((+3x)4)-15=0
We calculate terms in parentheses: -((+3x)4), so:
(+3x)4
We multiply parentheses
12x
Back to the equation:
-(12x)
We add all the numbers together, and all the variables
-2x-15=0
We move all terms containing x to the left, all other terms to the right
-2x=15
x=15/-2
x=-7+1/2

See similar equations:

| 1.92×x/1.6×0.8=3/2 | | 3q*2-10Q+60=0 | | 5x-13=78 | | 7(x-1)+8=5(7-x)+14 | | 7(x+1)+8=5(7-x)+14 | | 2/4=q/48 | | 58=-x/9 | | 11÷5y-60=y | | .219=0.00008x+0.2072 | | 4g-13=2g+51= | | -24=6yy= | | 5.7/3.6=x/3.2 | | 27=-u/2u= | | 6m+17/2=13 | | .219=(8)(10^-5)x+0.2072 | | 4y-16=2y-12 | | (x^2-8)(4-x)=0 | | 9k^2-12k+8k=0 | | (3x^2+4)-(2x+3)=0 | | 3*(y-1)=2(y-6) | | 7(x+16)=175 | | 9(t-3)=5(2t-1) | | 7m+4=23 | | 7m=4=23 | | 3m-2/7=2m-5 | | 8p-4=4p+4 | | -5w+16.8=4.3 | | x/4=8/3 | | 4x-14/50=10 | | x+x+x/2+x/8+3=300 | | .219=8E-05x+0.2072 | | n/4-3=3 |

Equations solver categories